CRIPTO Is a Marker of Chemotherapy-Induced Stem Cell Expansion in Non-Small Cell Lung Cancer - Francescangeli, Federica; De Angelis, Maria Laura; Rossi, Rachele; Sette, Giovanni; Eramo, Adriana; Boe, Alessandra; Guardiola, Ombretta; Tang, Tao; Yu, Shi-Cang; Minchiotti, Gabriella; Zeuner, Ann (Frontiers in Oncology, 2022)
Chemotherapy is the mainstay for the treatment of non-small cell lung cancer (NSCLC). However, NSCLC cells are either intrinsically chemoresistant or rapidly develop therapy resistance. Cancer stem cells (CSCs) are widely recognized as the cell population responsible for resistance to systemic therapies, but the molecular responses of CSCs to chemotherapeutic agents are largely unknown. We identified the embryonic protein CRIPTO in stem cell-enriched spheroid cultures of adenocarcinoma (AC) and squamous cell carcinoma (SCC) derived from NSCLC surgical specimens. The CRIPTO-positive population had increased clonogenic capacity and expression of stem cell-related factors. Stemness-related properties were also obtained with forced CRIPTO expression, whereas CRIPTO downregulation resulted in cell cycle blockade and CSCs death. Cell populations positive and negative for CRIPTO expression were interconvertible, and interfering with their reciprocal equilibrium resulted in altered homeostasis of cell expansion both in spheroid cultures and in tumor xenografts. Chemotherapy treatment of NSCLC cells resulted in reduction of cell number followed by increased CRIPTO expression and selective survival of CRIPTO-positive cells. In NSCLC tumor xenografts, chemotherapeutic agents induced partial cell death and tumor stabilization followed by CRIPTO overexpression and tumor progression. Altogether, these findings indicate CRIPTO as a marker of lung CSCs possibly implicated in cancer cell plasticity and post-chemotherapy tumor progression.